Maimonides' On coitus - Maimonides, Moses, 1135-1204, (The Medical Works of Moses Maimonides, 2018)
Moses Maimonides' On Coitus was composed at the request of an unknown high-ranking official who asked for a regimen that would be easy to adhere to, and that would increase his sexual potency, as he had a large number of slave girls. It is safe to assume that it was popular in Jewish and non-Jewish circles, as it survives in several manuscripts, both in Arabic and Judaeo-Arabic. The present edition by Gerrit Bos contains the original Arabic text, three medieval Hebrew translations, two Latin versions from the same translation (edited by Charles Burnett), and a Slavonic translation (edited by Will Ryan and Moshe Taube).